Analisis Pengaruh Earning Per Share (EPS), Debt To Equity Ratio (DER), Dan Price To Book Value (PBV) Terhadap Harga Saham (Studi Empiris Pada Perusahaan Sub Sektor Otomotif Dan Komponen Yang Terdaftar Di Bursa Efek Indonesia Tahun 2015-2018) - Iffatul Masrurah; M Agus Salim; Achmad Agus Priyono (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstractThe purpose of this research is to know the effect of Earning Per Share  (EPS), Debt to Equity Ratio (DER), Price to Book Value (PBV) to stock price. The dependent variable used is stock price, while the independent variables are Earning Per Share (EPS), Debt to Equity Ratio (DER), Price to Book Value (PBV). Research population is automotive and component sub sector companies listed in BEI years 0f 2015-2018 as many as 12 companies. Sampel obtained 12 companies by using purposive sampling technique. This research used secondary data. Data analisys technique used is multiple linear regression analysis and classic assumption test. The research results show that Earning Per Share (EPS) and Price to Book Value (PBV) had a significant positive effect on stock pricec to automotive and component sub sector companies listed in BEI years 0f 2015-2018. However Debt to Equity Ratio (DER) has no effect on stock price to automotive and component sub sector companies listed in BEI years 0f 2015-2018.Keywords: Earning Per Share (EPS), Debt to Equity Ratio (DER), Price to Book Value (PBV), Stock Price.